2014
DOI: 10.1103/physrevd.90.034025
|View full text |Cite
|
Sign up to set email alerts
|

QCD corrections to theBcto charmonia semileptonic decays

Abstract: We present a detailed analysis on the Bc meson semi-leptonic decays, Bc → ηc(J/ψ)ℓν, up to next-to-leading order (NLO) QCD correction. We adopt the principle of maximum conformality (PMC) to set the renormalization scales for those decays. After applying the PMC scale setting, we determine the optimal renormalization scales for the Bc → ηc(J/ψ) transition form factors (TFFs). Because of the same β0-terms, the optimal PMC scales at the NLO level are the same for all those TFFs, i.e. µ PMC r ≈ 0.8GeV. We adopt a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 80 publications
1
30
0
Order By: Relevance
“…For the B c → J/ψ form factors, they have been studied in a variety of approaches [106][107][108][109][110][111][112][113][114][115][116] (for earlier analysis focused on this decay mode see refs. [116][117][118][119]).…”
Section: Form Factorsmentioning
confidence: 99%
“…For the B c → J/ψ form factors, they have been studied in a variety of approaches [106][107][108][109][110][111][112][113][114][115][116] (for earlier analysis focused on this decay mode see refs. [116][117][118][119]).…”
Section: Form Factorsmentioning
confidence: 99%
“…The LHCb experiment can produce and reconstruct a large number of the B c meson events, and it provides a solid platform to study the properties of the B c meson precisely. A great deal of work has been done on various B c decays under different approaches, such as NRQCD approach [1,[11][12][13], the perturbative QCD approach (PQCD) [14][15][16][17], the relativistic quark model (RQM) [18][19][20][21], Light-cone sum rules (LCSR) [22], the nonrelativistic constituent quark model (NCQM) [23] and QCD sum rules (QCDSR) [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…for the decay constants, and 20) for the LCDAs. Here ∆ = 0 is for NDR scheme [49], and ∆ = 1 for the HV scheme [50].…”
Section: Jhep12(2017)012mentioning
confidence: 99%
“…Meanwhile the NRQCD factorization has been adopted in refs. [18][19][20][21][22][23][24][25][26], in which the non-perturbative physics reside in a few NRQCD matrix elements. The LHCb collaboration has started comprehensive experimental studies of the decays [27], and some phenomenological studies can be found in refs.…”
Section: Jhep12(2017)012mentioning
confidence: 99%